Cognitive Flexibility and Advice Network Centrality: The Moderating Role of Self-Monitoring - Hu, Saiquan; Zhong, Zhou; Zhang, Jin; Zheng, Xiaoying (Frontiers in Psychology, 2018)
This study examined the role of individuals’ cognitive flexibility and self-monitoring in shaping their workplace advice network centrality. Drawing on advice network generation theory, we hypothesized a positive relationship between cognitive flexibility and advice network centrality, and a moderation effect of self-monitoring on this relationship. Then, we collected two time-points data from insurance salesmen to test the hypotheses. As predicted, cognitive flexibility was positively associated with advice network centrality. Furthermore, this positive relationship was only significant for low self-monitoring individuals, but not for high self-monitoring individuals. These findings indicated that individuals with high cognitive flexibility were more likely to have central positions in the advice network; however, this effect was attenuated as their self-monitoring increased.